Transformasi Manajemen Sistem Pembelajaran Digital Berbasis Artificial Intelligence (AI) Dalam Meningkatkan Kualitas Pendidikan Modern - Ketut Sintia Devi; Desak Putu Gayatri Sintia Putri; Komang Darma Waspayanti Putri; Made Darma Waspayani Putri; I Komang Redi Prayoga; I Putu Prasita Yasa (Indonesian Journal Publisher, 2026)
The rapid advancement of digital technology has encouraged the integration of Artificial Intelligence (AI) into various aspects of education, including digital learning management systems. AI offers significant opportunities to enhance the effectiveness, flexibility, and quality of learning by supporting more personalized and data-driven educational practices. This study aims to analyze the implementation of AI in digital learning management and examine its contribution to improving the quality of modern education. The study employs a qualitative approach using a literature review method. Data were collected from relevant scientific sources, including journal articles, books, conference proceedings, and other academic publications, and analyzed using content analysis techniques. The findings indicate that AI plays an important role in supporting personalized learning through technologies such as intelligent tutoring systems, adaptive learning, learning analytics, and educational chatbots. In addition to enhancing learning effectiveness, AI contributes to curriculum management, assessment processes, and data-driven decision-making. However, its implementation continues to face several challenges, including limited technological infrastructure, uneven digital competencies among educators, and concerns related to data security and ethical issues. In conclusion, AI has considerable potential to transform digital learning management and improve educational quality. Its successful implementation requires supportive policies, capacity building for human resources, and adequate technological infrastructure to ensure sustainable and effective integration in education.